PERAN PENDIDIKAN KARAKTER DALAM MENGHADAPI TANTANGAN MORAL DI ERA DIGITAL - Roni Sahindra; Irna Br Napitupulu; Dinda Nabilah; Nurul Hifji Harahap; St. Rahmah (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
The digital era presents increasingly complex moral challenges for students, driven by unfiltered information exposure, the rise of instant gratification culture, and the weakening of traditional social control. Character education serves as a strategic approach to equip young generations with strong moral foundations in navigating these digital dynamics. This study aims to analyze the role of character education in strengthening students’ moral resilience and to identify potential obstacles encountered during its implementation in educational settings. A literature review method is employed to examine various academic sources on character development within the digital context. The findings indicate that character education effectively enhances students’ critical thinking, integrity, responsibility, and discipline when interacting with digital content. However, its implementation faces several challenges, including insufficient role modelling, limited collaboration between schools and parents, and inadequate technological competence among educators. Therefore, a comprehensive strategy is required, involving the integration of moral values into digital-based learning, improvement of teachers’ digital literacy, and reinforcement of partnerships among schools, families, and communities. In conclusion, character education is expected to serve as an effective solution for shaping morally grounded individuals capable of facing ethical challenges of the digital age.